2008
DOI: 10.1074/jbc.m801844200
|View full text |Cite
|
Sign up to set email alerts
|

Specific TRPC6 Channel Activation, a Novel Approach to Stimulate Keratinocyte Differentiation

Abstract: The protective epithelial barrier in our skin undergoes constant regulation, whereby the balance between differentiation and proliferation of keratinocytes plays a major role. Impaired keratinocyte differentiation and proliferation are key elements in the pathophysiology of several important dermatological diseases, including atopic dermatitis and psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 37 publications
(53 reference statements)
2
83
0
1
Order By: Relevance
“…In psoriatic skin lesions, the expression of TRPC6 is markedly reduced (Leuner et al, 2011). Activation of TRPC5 by hyperforin partially restores the disturbed keratinocyte differentiation in psoriatic lesions (Müller et al, 2008). This implies a therapeutic potential for TRPC6 agonist creams in the pharmacotherapy of psoriasis.…”
Section: Dietary Mgmentioning
confidence: 92%
“…In psoriatic skin lesions, the expression of TRPC6 is markedly reduced (Leuner et al, 2011). Activation of TRPC5 by hyperforin partially restores the disturbed keratinocyte differentiation in psoriatic lesions (Müller et al, 2008). This implies a therapeutic potential for TRPC6 agonist creams in the pharmacotherapy of psoriasis.…”
Section: Dietary Mgmentioning
confidence: 92%
“…Usually, the stimulation effects were observed at low doses of plant preparations with inhibitory effects at higher ones [47,48]. For example, it has been reported that hyperforin from H. perforatum can induce keratinocyte differentiation in vitro [49]. Stimulation of proliferation was found to be beneficial for normal cells or tissues which require rejuvenation and regeneration and it is undesirable for cancer cells due to promoting cancer malignization [48,50].…”
Section: Plant Extracts Protect Yeast Cells Against H 2 O 2 At Acidicmentioning
confidence: 99%
“…As a nonselective cation channel, TRPC6 is permeable for sodium and for calcium. Thus, it triggers calcium-dependent intracellular signaling processes necessary for cell differentiation (Leuner et al, 2007;Mü ller et al, 2008). In PC12 cells, hyperforin mimics NGF-induced cellular responses involved in neurite outgrowth (Leuner et al, 2007).…”
mentioning
confidence: 99%